ALIH KODE DAN CAMPUR KODE PADA PEMBELAJARAN SISWA SMP NEGERI 3 LAMBU KIBANG TULANG BAWANG BARAT - Effrina Yuricki (LPPM STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to find out the form of code switching and code mixing, and want to see the benefits or functions of its use in learning activities in SMP Negeri 3 Lambu Kibang Tulang Bawang Barat. The method used is qualitative, which is to describe the form of code switching and code mixing in learning activities. From the results of the classification of the form of data mixed using Lampung language code in the process of learning activities obtained, the form that often appears is in terms of word forms (24.13%), phrases (13.79%) and sentences (26.72%) and clauses and the abbreviation is not found at all. Whereas the result of the classification of the form of code switching using Lampung language that often appears is from the form of sentences around (14.65%) and words, phrases, clauses and abbreviations are not found at all. The function of mixing codes and Lampung language code switching in learning at Lambu Kibang Tulang Bawang Barat Junior High School is to establish intimacy, provide explanations, affirmation to students as well as understand and know material deeper for students.